tìm x biết: x+1/2019+x+2/2018+x+3/2017=x-1/2021+x-2/2022+x-3/2023
tìm x
(x+1)/2023 + (x+2)/2022=(x+3)/2021 + (x+4)/2020
\(\dfrac{x+1}{2023}+\dfrac{x+2}{2022}=\dfrac{x+3}{2021}+\dfrac{x+4}{2020}\\ \Leftrightarrow\dfrac{x+1}{2023}+1+\dfrac{x+2}{2022}+1=\dfrac{x+3}{2021}+1+\dfrac{x+4}{2020}+1\\ \Leftrightarrow\dfrac{x+1+2023}{2023}+\dfrac{x+2+2022}{2022}-\dfrac{x+3+2021}{2021}-\dfrac{x+4+2020}{2020}=0\\ \Leftrightarrow\left(x+2024\right)\times\left(\dfrac{1}{2023}+\dfrac{1}{2022}-\dfrac{1}{2021}-\dfrac{1}{2020}\right)=0\\ \Rightarrow x+2024=0:\left(\dfrac{1}{2023}+\dfrac{1}{2022}-\dfrac{1}{2021}-\dfrac{1}{2020}\right)\\ \Rightarrow x+2024=0\\ \Rightarrow x=-2024\)
`(x+1)/2023+(x+2)/2022=(x+3)/2021+(x+4)/2020`
`=>(x+1)/2023+1+(x+2)/2022+1=(x+3)/2021+1+(x+4)/2020+1`
`=>(x+2024)/2023+(x+2024)/2022=(x+2024)/2021+(x+2024)/2020`
`=>(x+2024)/2023+(x+2024)/2022-(x+2024)/2021-(x+2024)/2020=0`
`=>(x+2024).(1/2023+1/2022-1/2021-1/2020)=0`
Vì `1/2023+1/2022-1/2021-1/2020` `\ne` `0`
`=> x+2024=0`
`=>x=-2024`
Tìm x, biết:
( \(\dfrac{1}{2}\) + \(\dfrac{1}{3}\) + \(\dfrac{1}{4}\) + ... + \(\dfrac{1}{2023}\) ) . x = \(\dfrac{2022}{1}\) + \(\dfrac{2021}{2}\) + \(\dfrac{2020}{3}\)
+ ... + \(\dfrac{1}{2022}\)
(\(\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2023}\)). x = (\(\dfrac{2021}{2}+1\))+(\(\dfrac{2020}{3}+1\))+....+(\(\dfrac{1}{2022}+1\))
(\(\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2023}\)). x = \(\dfrac{2023}{2}\)+\(\dfrac{2023}{3}\)+....+ \(\dfrac{2023}{2022}\)
(\(\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2023}\)). x = 2023.( \(\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2023}\))
vậy x= 2023
tìm x biết
x-1/2019+x-2/2018+x-3/2017=3
tìm x biết
x-1/2019+x-2/2018+x-3/2017=3
\(\dfrac{x-1}{2019}+\dfrac{x-2}{2018}+\dfrac{x-3}{2017}=3\)
\(\Leftrightarrow\left(\dfrac{x-1}{2019}-1\right)+\left(\dfrac{x-2}{2018}-1\right)+\left(\dfrac{x-3}{2017}-1\right)=0\)
\(\Leftrightarrow\dfrac{x-1-2019}{2019}+\dfrac{x-2-2018}{2018}+\dfrac{x-3-2017}{2017}=0\)
\(\Leftrightarrow\dfrac{x-2020}{2019}+\dfrac{x-2020}{2018}+\dfrac{x-2020}{2017}=0\)
\(\Leftrightarrow\left(x-2020\right)\left(\dfrac{1}{2019}+\dfrac{1}{2018}+\dfrac{1}{2017}\right)=0\)
Vi \(\dfrac{1}{2019}+\dfrac{1}{2018}+\dfrac{1}{2017}\ne0\)
nên \(x-2020=0\)
\(\Leftrightarrow x=2020\)
Vậy ...
tìm x 2-x/2021 -1 = 1-x/2022 - x/2023
=>\(\left(\dfrac{2-x}{2021}-1\right)=\left(\dfrac{1-x}{2022}-1\right)+\left(1-\dfrac{x}{2023}\right)\)
=>2023-x=0
=>x=2023
Tìm x, biết: a) 121-(115+x)= 3x-(25-9-5x)-8
b)2x+2.3x+1.5x = 10800
c) (3|x-1/2) . (8/15-1/5)+2/3-1
d) x+1/2022 + x+2/2021= x+3/2020 + x+4/2019
\(a,121-\left(115+x\right)=3x-\left(25-9-5x\right)-8\\ 121-115-x=3x-25+9+5x-8\\ 6-x=8x-24\\ 8x+x=-24-6\\ 9x=-30\\ x=-\dfrac{30}{9}=-\dfrac{10}{3}\\ ----\\ b,2^{x+2}.3^{x+1}.5^x=10800\\ \left(2.3.5\right)^x.2^2.3=10800\\ 30^x.12=10800\\ 30^x=\dfrac{10800}{12}=900=30^2\\ Vậy:x=2\)
Tìm x biết
\(\frac{x+4}{2019}+\frac{x+3}{2020}=\frac{x+2}{2021}+\frac{x+1}{2022}\)
\(\frac{x+4}{2019}+\frac{x+3}{2020}=\frac{x+2}{2021}+\frac{x+1}{2020}\)
\(\Leftrightarrow(\frac{x+4}{2019}+1)+(\frac{x+3}{2020}+1)=(\frac{x+2}{2021}+1)+(\frac{x+1}{2022}+1)\)
\(\Leftrightarrow\frac{x+2023}{2019}+\frac{x+2023}{2020}=\frac{x+2023}{2021}+\frac{x+2023}{2022}\)
\(\Leftrightarrow\frac{x+2023}{2019}+\frac{x+2023}{2020}-\frac{x+2023}{2021}-\frac{x+2023}{2022}=0\)
\(\Leftrightarrow\left(x+2023\right)\left(\frac{1}{2019}+\frac{1}{2020}-\frac{1}{2021}-\frac{1}{2020}\right)=0\)
\(\Leftrightarrow x+2023=0\)
\(\Leftrightarrow x=-2023\)
Nhầm đề :( Với bước thứ 4 sửa thành ( 1/2019 + 1/2020 - 1/2021 - 1/2022 )
\(\frac{x+4}{2019}+\frac{x+3}{2020}=\frac{x+2}{2021}+\frac{x+1}{2022}\)
\(\Leftrightarrow\)\(\frac{x+4}{2019}+\frac{x+3}{2020}+2=\frac{x+2}{2021}+\frac{x+1}{2022}+2\)
\(\Leftrightarrow\)\(\left(\frac{x+4}{2019}+1\right)+\left(\frac{x+3}{2020}+1\right)=\left(\frac{x+2}{2021}+1\right)+\left(\frac{x+1}{2022}+1\right)\)
\(\Leftrightarrow\)\(\left(\frac{x+4}{2019}+\frac{2019}{2019}\right)+\left(\frac{x+3}{2020}+\frac{2020}{2020}\right)\)\(=\)\(\left(\frac{x+2}{2021}+\frac{2021}{2021}\right)+\left(\frac{x+1}{2022}+\frac{2022}{2022}\right)\)
\(\Leftrightarrow\)\(\frac{x+2023}{2019}+\frac{x+2023}{2020}=\frac{x+2023}{2021}+\frac{2023}{2022}\)
\(\Leftrightarrow\)\(\frac{x+2023}{2019}+\frac{x+2023}{2020}-\frac{x+2023}{2021}-\frac{x+2023}{2022}=0\)
\(\Leftrightarrow\) \(\left(x+2023\right).\left(\frac{1}{2019}+\frac{1}{2020}-\frac{1}{2021}-\frac{1}{2022}\right)=0\)
\(\Leftrightarrow\)\(x+2023=0\) ( Vì \(\frac{1}{2019}+\frac{1}{2020}-\frac{1}{2021}-\frac{1}{2022}\ne0\))
\(\Leftrightarrow\)\(x=-2023\)
Vậy x = -2023
Tìm x biết :
[1/2 + 1/3 + .......+ 1/2019]x = 2018/1 + 2017/2 + .......+ 1/2018
1 tìm x biết
x-4/2021+x-3/2020=x-2/2019+x-1/2018
giúp mk vs lm ơn